2012
DOI: 10.5120/4600-6802
|View full text |Cite
|
Sign up to set email alerts
|

Methods to obtain basic Probability Assignment in Evidence Theory

Abstract: Dempster-Shafer Theory (DST) of Evidence is a powerful and flexible mathematical tool for handling uncertainty, impreciseness, and incomplete information. It can be used when both epistemic and aleatory uncertainties are present in the problem under consideration. The fundamental and important object of this theory of evidence is the primitive function called basic probability assignment (bpa). In the absence of empirical data, experts in related fields provide necessary information (bpa). However how to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Ali and P. Dutta proposed a method to determine BPA when minimum, maximum and most likely values of the parameter are known. They developed an extended version of uncertainty measurement in evidence theory in order to calculated total uncertainty of the body of evidence [1]. A.O.…”
Section: Previous Workmentioning
confidence: 99%
“…Ali and P. Dutta proposed a method to determine BPA when minimum, maximum and most likely values of the parameter are known. They developed an extended version of uncertainty measurement in evidence theory in order to calculated total uncertainty of the body of evidence [1]. A.O.…”
Section: Previous Workmentioning
confidence: 99%
“…T. Ali et al, proposed a method of deciding a BPA in the context in which minimal value, maximum value and arithmetic operator in an approximate value are recognized [3].…”
Section: Methods Of Deciding a Bpamentioning
confidence: 99%
“…Suppose that in a DST, the whole set consisting of mutually exclusive propositions is Θ and that 2 θ is the power set of Θ, which includes all possible propositions, the basic probability assignment m assigned to an interest element has four kinds of the following characteristics [3,4].…”
Section: Requirements Of Dstmentioning
confidence: 99%
“…They applied it to color image segmentation [4]. Ali and Dutta suggested a way to determine BPA when the operators of minimum, maximum, and approximate values were recognized [5]. Jiang et al showed a way to determine BPA with measuring a distance between subject properties and tested sample data [6].…”
Section: Cases Of Bpa Determinationmentioning
confidence: 99%